N-Acetylcysteine May Regulate Altered Meteorin-Like Levels in Testicular Tissue due to Aluminum Exposure - Yalcin, Tuba; Kaya, Sercan; Kuloglu, Tuncay; Yigin, Akin (Springernature, 2023)
Aluminum (AL) is a heavy metal known to have toxic effects on the reproductive system. It is known that N-acetylcysteine (NAC), which has an antioxidant effect, is a useful chelator for heavy metals. This study aimed to determine whether NAC may reduce AL-induced oxidative stress, inflammation, and germ cell apoptosis in testicular tissues and its effects on meteorin-like (METRNL) levels, which are known to play a role in energy metabolism. In this experimental study, 28 Sprague-Dawley male rats were randomly divided into 4 groups (n = 7): control, AL (30 mg/kg/day AL), AL + NAC (30 mg/kg/day AL + 150 mg/kg/day NAC), and NAC (150 mg/kg/day NAC). All AL and NAC applications were performed intraperitoneally for 14 days. At the end of the experiment, the effects of AL and/or NAC applications on testicular tissue were examined histomorphometrically, histopathologically, immunohistochemically, and biochemically. It was determined that AL exposure caused histomorphometric and histopathological changes, oxidative stress, apoptosis of germ cells, and inflammation in testicular tissues. In addition, AL caused an increase in METRNL levels. It was determined that NAC treatment significantly reduced the negative effects of AL. NAC therapy may be a protective strategy in reproductive toxicity due to AL exposure.
Keywords: Aluminum; Meteorin-like; N-Acetylcysteine; Testicular tissue